Pengaruh Literasi Digital, Adopsi Pembayaran QRIS, dan Preferensi Konsumen terhadap Peningkatan Transaksi Digital di Pasar Kreneng Denpasar - Ni Nyoman Ayu Pradnya Sulaksmi Dewi; Ni Ketut Anjani (Journal Of Business, Finance, and Economics (JBFE), 2025)
Digital transformation in Pasar Kreneng Denpasar is influenced by digital literacy, QRIS payment adoption, and consumer preferences, which, despite being supported by technological developments and government policies, still face challenges related to digital capabilities and cash-based transaction habits, thus requiring continuous education and assistance. The purpose of this study is to examine the effect of digital literacy, QRIS payment system adoption, and consumer preferences on the increase in digital transactions at Pasar Kreneng Denpasar. This study employs a quantitative approach conducted at Pasar Kreneng Denpasar with a population of 3,168 traders and consumers and a sample of 97 respondents selected through purposive sampling, using primary and secondary data collected via Likert-scale questionnaires and documentation, which were then analyzed using SPSS through validity and reliability tests, descriptive analysis, classical assumption tests, and multiple linear regression to examine the effects of digital literacy, QRIS adoption, and consumer preferences on the increase in digital transactions. The results indicate that digital literacy, QRIS payment adoption, and consumer preferences, both partially and simultaneously, have a positive and significant effect on increasing digital transactions at Pasar Kreneng Denpasar, with consumer preferences being the most dominant factor; therefore, the better the technological understanding, the wider the use of QRIS, and the stronger consumers’ preference for digital payments, the higher the intensity of digital transactions in this traditional market.